The Protective Factors of Bullying Victimization Experiences on Mental Health among Adolescents: A Decade of Systematic Review - Munawaroh, Eem; Sutoyo, Anwar; Arinata, Firdian Setiya; Karomah, Anggun; Damayanti, Silviana; Nitami, Luvieta Zulgya (KONSELOR, 2024)
Despite extensive research on the mental health consequences of bullying victimization, there is limited information on the protective factors that may mitigate these negative outcomes. This systematic review seeks to identify factors that can buffer the impact of bullying victimization on adolescent mental health. Articles were selected from the Scopus and Pubmed databases, covering studies published between 2014 and 2024. After applying the inclusion and exclusion criteria, 11 studies were found that focused on protective factors against the mental health effects of bullying among adolescents. The review reveals two major categories of protective factors: personal strengths and social support. Personal strengths include traits such as resilience, forgiveness, and religiosity, while social support involves factors such as student connectedness, parental psychological control, increased autonomy support, strong parent-child attachment, and the presence of multiple supportive adults. The findings suggest that schools should focus on building personal strengths and enhancing social support systems as key strategies to protect students from the adverse mental health effects of bullying, particularly through the improvement of counseling services and the creation of support programs.